PP22 Development and Optimization of a CE-DAD Method for the Determination of Neurotransmitters in Insect and Vertebrate Brains - Benavides Vesga, Mariana; Carazzone, Chiara (Revista Productos Naturales, 2025)
Advances are presented in the development of a capillary electrophoresis method with diode array detection (CE-DAD) for the determination of neurotransmitters in rat, fish, and insect brains. The optimized method allows the separation of dopamine, tyrosine, and tryptophan in 20 minutes, with detection and quantification limits of 100 and 500 ppb, respectively. Various separation conditions and sample preparation methods were evaluated, including extraction with formic acid and clean-up using SPE, highlighting the importance of matrix reduction for UV-based analysis. This technique represents an accessible alternative for the analysis of neurotransmitters in complex biological matrices.